TYPES OF NEOLOGISMS AND THEIR CLASSIFICATION IN ENGLISH AND UZBEK (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Neologisms play a crucial role in linguistic evolution, reflecting social, cultural, and technological changes. This paper explores thevarious classifications of neologisms based on linguistic theories, particularly focusing on English and Uzbek languages. The studyanalyzes word formation processes such as affixation, compounding, borrowing, and semantic shifts. The comparative approachhighlights similarities and differences in neologism formation between two languages. By employing a qualitative comparativemethodology, the paper provides insights into the role of neologisms in linguistic enrichment and their impact on communication.